Answer:
x = -4
Explanation:
Square both sides:
![(√(-5-2x))^2 =(√(-1-x) )^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g8i70113fksj96hol0zz211gck7ffcvly1.png)
The square root and the square will cancel to leave simply the argument within the square root:
-5 - 2x = -1 - x
Now simply isolate the variable x:
x = -5 + 1 = -4
Check to see if x = -4 will work:
![√(-5-2*(-4)) =√(-1-(-4))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qx66u8tpz98ataeur0lpse57mp8bviun5o.png)
![√(3) =√(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7a65ivnfey7z2486ddgfsozrkama47rwtr.png)
This works, so we know that x = -4 is a solution.
Hope this helps!